2008
DOI: 10.2746/095777308x272120
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus equi pneumonia in an adult horse

Abstract: Summary A 20‐year‐old, Thoroughbred mare in the fifth month of gestation was examined for weight loss, pyrexia and lethargy. Physical examination, ultrasonography and radiography revealed a severe abscessing pneumonia and a dead fetus. The mare did not respond to symptomatic treatment and died suddenly. Necropsy revealed multifocal pulmonary abscessation. Rhodococcus equi was isolated from the lungs, liver and kidneys. Specific immune function of the mare and presence of the virulence associated protein A (Vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Recent evidence has shown that foals are interferon gamma deficient at birth (Breathnach et al 2006), and, since this is the premiere Th-1 cytokine, this may contribute to susceptibility of young foals on endemic farms to R. equi infection. Although the mare of this report (Waldridge et al 2008) had adequate globulin levels, she had persistent lymphopenia. Reduction of one immunoglobulin isotype may not result in an overall hypogammaglobulinaemia, but specific isotype immunoglobulin measurement will identify if a host has reduced globulin production.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Recent evidence has shown that foals are interferon gamma deficient at birth (Breathnach et al 2006), and, since this is the premiere Th-1 cytokine, this may contribute to susceptibility of young foals on endemic farms to R. equi infection. Although the mare of this report (Waldridge et al 2008) had adequate globulin levels, she had persistent lymphopenia. Reduction of one immunoglobulin isotype may not result in an overall hypogammaglobulinaemia, but specific isotype immunoglobulin measurement will identify if a host has reduced globulin production.…”
mentioning
confidence: 64%
“…The report by Waldridge et al (2008) of a 20-year-old broodmare with disseminated Rhodococcus equi infection makes an important contribution to the literature, because it reports an atypical presentation and progression of this disease in an adult horse. Although few reports of R. equi in adult horses exist it is important to consider this differential diagnosis for an adult with severe sepsis and pneumonia.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the presence of blood in the airways, due to previous episodes of pulmonary haemorrhage (EIPH), which occur frequently in racehorses, promotes the onset of airway inflammation (MacKane and Slocombe 1999) and represents an ideal pabulum for bacterial growth. Several aerobic bacterial species responsible for respiratory infection were identified in horses: among these, β-haemolytic Streptococci, Pasteurellaceae, Klebsiella pneumoniae, Rhodococcus equi and Enterobacteriaceae should be mentioned (Sweeney et al 1991;Chaffin and Carter 1993;Lakritz et al 1993;Lavoie et al 1994;Raidal 1995;Raclyeft and Love 2000;Vengust et al 2002;Waldridge et al 2008). Early identification of a pneumonic process and of the causative agent, and prompt institution of a specific antimicrobial therapy, are fundamental for the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Reported cases have involved immune suppression 6,7 or concurrent pregnancy 13 . Pulmonary R. equi infection is commonly not diagnosed until necropsy where it is an incidental finding 14–17 …”
mentioning
confidence: 99%